PEMBENTUKAN KARAKTER TOLERANSI MELALUI PELAKSANAAN PENDIDIKAN AGAMA KATOLIK DAN BUDI PEKERTI - Yohana Yosiphanungkas Bahari Mandayu; Yohanes Bahari; Rustiyarso Rustiyarso (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract:This research aims to describe how teacher’s intervention and habituation which leads to tolerance building and tolerance character which formed after giving intervention and habituation. This research is qualitative descriptive study. This research uses observation, in depth-interview, and documentation technique. The result indicates that there are intervention and habituation from teacher of Catholic Religion and Character Education. The interventions are good advice, appeals to congratulate and visit on other’s celebration day, prohibition of humiliating others, discourse respecting other religions. Teaching interventions in the lower class are designed through emphasis of Love and Ten Commandment, correlating the subject, by giving real examples, and applying reading aloud methods. In the high class, these are designed through direct practices, such as using Contacting Book, applying heterogeneous cooperative group, tolerant assignment and democratic practice, moral practice and reflection. The habituation is practice through speech and action. The habituation processes are formed teacher’s exemplary, congratulate on other’s celebration day, saying 3 magical words “Please, Sorry and Thank You”. The lower class habituations are designed through reminding and appreciating students. In the high class, the teacher gives opportunity to blend each other, asking and delivering idea(s). The tolerance character of students are formed mutual respect, love of peace and unity, friendly, tolerance, empathize and democratic, having high social awareness and cooperate. Keywords: Character Education, Catholic Religion and Character Education, Tolerance